The WPA position paper on spirituality and religion in psychiatry: a North American perspective. Issue 6 (3rd July 2017) - Peteet, John R.
ABSTRACT: The WPA position statement is a clear challenge for psychiatrists to recognize how religion/spirituality (R/S) is relevant to their work. North American psychiatry has shown progress related to each principle articulated in the statement, especially in the areas of research and scholarship. However, most advances are yet to be widely implemented or coordinated, so that the statement offers valuable encouragement and direction in moving forward.